Hypergeo: context-aware access to geographic information for mobile users - Rodrigues, Helena (2003)
The Hypergeo project aimed at providing technical tools to enable value-added, location-based information services to mobile users. Existing approaches are typically based on obtaining some information about user context and then using it to select some appropriate content from a centralised location-dependent source to satisfy user needs. Such systems are limited by the scalablity and flexibility issues raised by the use of a centralised source. In this paper we describe the Hypergeo system that brings together the current concept of location-based service, a service location infrastructure and user contextual information to provide a pro-active, location-sensitive information service that we consider to be better suited for mobile users. Our approach was to develop the Hypergeo system on top of a service location infrastructure capable of allowing applications to select Internet services that are associated with users' current location. Information services, developed and operated in an independent way by third-party entities, are integrated into a web portal to form a location-sensitive information service. With this work we produced guidelines that can be followed by applications to customise themselves when exploiting different user context dimensions, such as location and activity trends, to adapt their behaviour to mobile users.